Literary study of the poem Liqiliqi in Suma arusa - Machaca, Cesar (2019)
Aymara poetry happened to be a vindication to a poetic tendency that seeks its own canons and literary resources for its particularity centered on the relationship between man, nature and other living beings. The state and private publications provoked this situation. Reason why, we seek to describe the poem Liqiliqi, in Suma arusa (MEDP, 2006), for this qualitative methodology was chosen, the technique that was used was documentary research and the document analysis file. The result shows that the literary resources that are used in the Liqi liqi poem are repetition and metaphor, by the nature of language and religiosity. The first, denotes the cultural significance of the liqi liqi, because it announces the presence of living beings: people, hail and the fox. The second, indicates the habitat of the living being in an integrating and horizontal way.